Poverty, institutions, and the environmental-resource base - Dasgupta, Partha (World Bank WashingtonUS, 1994)
Seeks to identify possible links between rural poverty, fertility behaviour, and the local environmental resource base in poor countries. Argues that poverty and institutional failure are both moot causes of environmental degradation and that the latter may well be a cause (as well as an effect) of high fertility rates.